THE EFFECT OF INTRINSIC MOTIVATION AND SELF EFFICACY ON EMPLOYEE PERFORMANCE THROUGH WORK DEMAND AS INTERVENING VARIABLE - Hendra Wijaya; Andhy Tri Adriyanto (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The objective of this research aims to determine the effect of Intrinsic Motivation and Self Efficacy on Employee Performance with Work Demand as Intervening Variable. The research location is in Demak Regency. The population used is the staff of the Education and Training Agency of Demak Regency. The sample was taken from 59 respondents. The research data came from two sources, namely primary data and secondary data. The research is quantitative research. The sampling method used a purposive random sampling technique. The collected data is then analyzed using Structural Equation Modeling (SEM) with Smart PLS software. The result of this study shows Intrinsic Motivation has no effect on Work Demand, Self-Efficacy has a strong positive and significant effect on Work Demand, Work Demand has a strong enough, positive and significant effect on Employee Performance, Intrinsic Motivation has a fairly strong positive and significant effect on Employee Performance, and Self-Efficacy has a significant and positive effect on Employee Performance.